The relative importance of central nervous catecholaminergic and cholinergic mechanisms in drinking in response to antiotensin and other thirst stimuli. - Fitzsimons, J T (1975)
1. Intracranial or subcutaneous doses of atropine or atropine methyl nitrate that were fully effective at preventing drinking in response to intracranial carbachol did not block angiotensin-induced drinking. 2. The nicotinic antagonist dihydro-beta-erythroidine given intracranially affected neither angiotensin- nor carbachol-induced drinking. 3. The dopaminergic antagonists haloperidol and spiroperidol injected intracranially blocked angiotensin-induced drinking but did not affect carbachol-induced drinking. 4. Angiotensin- and carbachol-induced drinking were unaffected by alpha- or beta-adrenergic antagonists except at toxic doses. 5. Destruction of catecholaminergic neurones with 6-hydroxydopamine markedly reduced angiotensin-induced drinking, but had relatively little effect on carbachol-induced drinking. 6. Intracranial haloperidol reduced the amount of water drunk in response to overnight deprivation of water, but did not affect feeding in response to overnight starvation or to intracranial noradrenaline. 7. Drinking following overnight water deprivation was unaffected by intracranial alpha- or beta-adrenergic antagonists. 8. Preventing dopaminergic transmission with intracranial haloperidol decreased the water to food ratio of the rat's intake after overnight starvation, whereas increasing the dopamine levels with the combination of FLA-63 and L-DOPA increased the ratio. 9. Intraventricular dopamine in large amounts caused the water-replete rat to drink. 10. It is concluded that among the many functions of dopaminergic systems in the brain is a role in the control of water intake, and that these systems participate in an important way in drinking in response to angiotensin.